Contribution of Endocannabinoid Gene Expression and Genotype on Low Back Pain Susceptibility and Chronicity. Issue 1 (January 2018) - Ramesh, Divya; D'Agata, Amy; Starkweather, Angela R.; Young, Erin E.
Abstract : Background: A major research emphasis has been focused on defining the molecular changes that occur from acute to chronic pain to identify potential therapeutic targets for chronic pain. As the endocannabinoid system is dynamically involved in pain signaling, a plausible mechanism that may contribute to chronic pain vulnerability involves alterations in the amount of circulating endocannabinoids. Therefore, this study sought to examine cannabinoid type 1 ( CNR1 ), type 2 ( CNR2 ) receptors, fatty acid amide hydrolase ( FAAH ), and the vanilloid receptor (transient receptor potential cation channel subfamily V member 1 [ TRPV1 ]) gene expression profiles among individuals with acute and chronic low back pain (cLBP) at their baseline visit. We also assessed associations among selected single nucleotide polymorphisms (SNPs) of FAAH and CNR2 and measures of somatosensory function and self-report pain measures. Using a previously established quantitative sensory testing protocol, we comprehensively assessed somatosensory parameters among 42 acute LBP, 42 cLBP, and 20 pain-free participants. Samples of whole blood were drawn to examine mRNA expression and isolate genomic DNA for genotyping. CNR2 mRNA was significantly upregulated in all LBP patients compared with controls. However, FAAH mRNA and TRPV1 mRNA were significantly upregulated in cLBP compared with controls. A significant association was observed between FAAH SNP genotype and self-report pain measures, mechanical and cold pain sensitivity among LBP participants. cLBP participants showed increased FAAH and TRPV1 mRNA expression compared with acute LBP patients and controls. Further research to characterize pain-associated somatosensory changes in the context of altered mRNA expression levels and SNP associations may provide insight on the molecular underpinnings of maladaptive chronic pain.